Controlling Stem Cell-mediated Bone Regeneration through Tailored Mechanical Properties of Collagen Scaffolds - Sun, Hongli (2013)
Mechanical properties of the extracellular matrix (ECM) play an essential role in cell fate determination. To study the role of mechanical properties of ECM in stem cell-mediated bone regeneration, we used a 3D in vivo ossicle model that recapitulates endochondral bone formation. Three-dimensional gelatin scaffolds with distinct stiffness were developed using 1-Ethyl-3-[3-dimethylaminopropyl] carbodiimide hydrochloride (EDC) mediated zero-length crosslinking. The mechanical strength of the scaffolds was significantly increased by EDC treatment, while the microstructure of the scaffold was preserved. Cell behavior on the scaffolds with different mechanical properties was evaluated in vitro and in vivo. EDC-treated scaffolds promoted early chondrogenic differentiation, while it promoted both chondrogenic and osteogenic differentiation at later time points. Both micro-computed tomography and histologic data demonstrated that EDC-treatment significantly increased trabecular bone formation by transplanted cells transduced with AdBMP. Moreover, significantly increased chondrogenesis was observed in the EDC-treated scaffolds. Based on both in vitro and in vivo data, we conclude that the high mechanical strength of 3D scaffolds promoted stem cell mediated bone regeneration by promoting endochondral ossification. These data suggest a new method for harnessing stem cells for bone regeneration in vivo by tailoring the mechanical properties of 3D scaffolds.